Iron Deficiency in Patients Presenting with Somatic Symptoms and their Outcome with IV Iron Therapy - Iqra Kokhar, Aneel Kumar, Irfana, Bashir Ahmed Shaikh, Imdad Ali Ansari, Aftab Shah (Pakistan Journal of Medical & Health Sciences, 2023)
Objectives: To determine the effect of IV iron therapy on patients with Iron deficiency presenting with somatic symptoms. Materials and Methods: The design of this study was The Quasi-experimental study design and this study was conducted in Shaheed Mohtarma Benazir Bhutto Medical University, Larkana. This study was conducted in the duration of 6 months from July 2022–Dec 2022. Totally 90 patients were enrolled. 5ml venous blood sample were collected from of each patient and sent to laboratory of the hospital for complete blood count and serum ferritin level. Patients with iron deficiency were treated with IV iron. Then after eight-week treatment the patients were followed again and 5ml blood were collected in EDTA containing tube. Serum ferritin level was evaluated again at the end of 8 weeks. Somatic scoring scale was used to assess somatic symptom burden before and after IV iron therapy. Results: Out of 90 patients, 40.0% were male and 60.0% were female with mean age of 39.70± 7.30 years. Most of the patients were of age group 41-50 years, followed by the age group of 31-40 years and least number of patients were of age group of 20-30 years. The mean difference of somatic score of our enrolled patients were 7.01±0.33 with P-value of <0.05. The mean serum Ferritin difference between Pre-Treatment and Post-Treatment were found 37.28±-2.6 (ng/ml) with P-value of <0.05. Practical implication: The present study will help the doctors to treat the patients with Iron deficiency presenting with somatic symptoms on priority basis by using IV iron therapy. That will lead to early treatment of the patients and also avoid further complication and miss diagnosis of the patients. Conclusion: It is concluded that patients presenting with somatic symptoms and having iron deficiency improved promptly with IV iron therapy. Keywords: Iron deficiency, somatic symptoms, IV Iron therapy, serum Ferritin, Somatic Scoring scale